Ultra-low power and reliable magnetic based interconnects for nano-scale technologies. (August 2019) - Jamshidi, Vahid; Fazeli, Mahdi
Abstract: As technology shrinks toward nanometer scales, the delay and power consumption in logic gates reduces, while they follow an increasing trend in global interconnects. Consequently, on-chip interconnects have become a bottleneck from delay and power consumption points of view. In addition, due to reduced distance between adjacent wires in Nano-Scale technology, the effect of crosstalk noise has brought serious reliability challenges. In this paper, we propose an ultra-low power and reliable interconnect using magnetic based Driver-Receiver circuits and current mode signaling. The simulation results for 22-nm technology through comparison with the previous work shows significant superiority of the proposed interconnect considering delay, power consumption, and crosstalk robustness.